Association of inflammatory bowel disease and related medication exposure with risk of Alzheimer's disease: An updated meta-analysis - Xing, Yinghao; Li, Pei; Jia, Yuanyuan; Zhang, Kexin; Liu, Ming; Jiang, Jingjing (Frontiers in Aging Neuroscience, 2023)
Background Chronic systemic inflammation may be associated with neurocognitive decline, but the relationships between inflammatory bowel disease and related medications and the risk of Alzheimer's disease remain unclear. Methods We performed a meta-analysis to evaluate the associations of ulcerative colitis, Crohn’s disease and related medications with risk of Alzheimer's disease. We identified cohort and case-control studies by searching PubMed, Embase and Web of Science up to August 2022. Results Seven eligible studies with 20,174 cases of Alzheimer's disease were included in the meta-analysis. Six studies reported the association between ulcerative colitis and risk of Alzheimer's disease; five studies reported the association between Crohn’s disease and risk of Alzheimer's disease. Meta-analysis combining these studies did not reveal any significant association of ulcerative colitis or Crohn’s disease with risk of Alzheimer's disease. The pooled RRs were 1.16 (95%CI: 0.96, 1.41) and 1.17 (95%CI: 0.84, 1.62) for ulcerative colitis and Crohn’s disease, respectively. High heterogeneity was detected across the studies. Of note, there was an inverse association between inflammatory bowel disease related medication exposure and risk of Alzheimer's disease. The pooled RR for Alzheimer's disease was 0.86 (95%CI: 0.75, 0.99). No publication bias was detected. Conclusion This study does not support the association of ulcerative colitis and Crohn’s disease with the risk of Alzheimer's disease. However, medication treatment for inflammatory bowel disease might be associated with a lower risk of Alzheimer's disease.